2018
DOI: 10.1371/journal.pone.0200586
|View full text |Cite|
|
Sign up to set email alerts
|

Educational benefits for nurses and nursing students of the dementia supporter training program in Japan

Abstract: In Japan, which is thought to be a rapidly growing super-aging society, a national campaign named “the Dementia Supporter Caravan” has been deployed. The aim of this study was to assess the educational benefits of the dementia supporter training program for nurses and nursing students. We conducted dementia supporter training, and measured knowledge and attitudes regarding people with dementia as educational benefits pre- and post-training. Data sets of 134 nursing students and 63 nurses were analyzed. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 20 publications
1
37
0
1
Order By: Relevance
“…This suggests that being informed about symptoms of dementia does not necessitate better understanding of the needs of dementia patients nor alleviates the misconceptions that one may have towards dementia. Furthermore, it implies that interventions targeted at dementia caregivers should place more emphasis on the caregiving considerations and needs of dementia patients, in order to improve quality of care provided by caregivers (Chodosh et al, 2007;Gibbons et al, 2005;Matsuda et al, 2018). These interventions should also seek to inform caregivers on the non-symptomatic traits of dementia so as to alleviate caregivers subjective burden which may arise from mismatched expectations (Chiu et al, 2013;S€ orensen & Conwell, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that being informed about symptoms of dementia does not necessitate better understanding of the needs of dementia patients nor alleviates the misconceptions that one may have towards dementia. Furthermore, it implies that interventions targeted at dementia caregivers should place more emphasis on the caregiving considerations and needs of dementia patients, in order to improve quality of care provided by caregivers (Chodosh et al, 2007;Gibbons et al, 2005;Matsuda et al, 2018). These interventions should also seek to inform caregivers on the non-symptomatic traits of dementia so as to alleviate caregivers subjective burden which may arise from mismatched expectations (Chiu et al, 2013;S€ orensen & Conwell, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the debilitating symptoms of dementia and the progressive nature of the disease, persons with dementia typically require considerable care as their condition deteriorates (Ag€ uero-Torres et al, 1998). In this context, it has been reported that knowledge of dementia is important in facilitating the care management of persons with dementia (Chodosh et al, 2007;Gibbons, Teri, Logsdon, & McCurry, 2005;Matsuda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Based on interviews of owners/managers and staff members of CVSs, a previous research indicated that the CVS staff do not contact CGSCs due to lack of knowledge and relationship with CGSCs. 17 In Japan, the dementia friend initiatives to build dementiafriendly communities mainly provide the dementia supporter training program; 18,19 the purpose of this program is to increase dementia awareness. The program is typically a 90-min face-to-face lecture with video material, which teaches the epidemiology and symptoms of dementia and the appropriate way to interact with people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…20 Because healthcare professionals working for CGSCs provide the dementia supporter training program in many cases, the program may contribute to promoting cooperation through building relationships between CVSs and CGSCs, in addition to deepening the understanding of dementia. Although previous studies have examined the effects of the dementia education programs on knowledge and attitudes about dementia, 3,18,19,21 the effects of cooperation with healthcare professionals have not been examined. In this study we aimed to examine whether participation in the dementia supporter training programs promote the cooperation between CVSs and CGSCs.…”
Section: Introductionmentioning
confidence: 99%